1988
DOI: 10.1084/jem.168.5.1607
|View full text |Cite
|
Sign up to set email alerts
|

Alternative V kappa gene rearrangements in a murine B cell lymphoma. An explantation for idiotypic heterogeneity.

Abstract: The diversity ofthe antigen binding portion ofthe Ig molecule is generated through the recombination of multiple discontinuous gene segments (1, 2). The heavy chain variable (V) region coding sequence is formed when one of hundreds of VN regions combines with one of 15-20 D regions and one of 4J . regions to create a complete VDJ segment (3, 4) . Light chain recombination proceeds in a similar fashion between V,, andJL segments (5). These events occur in a well-defined order with DJ . rearrangement preceding V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…It has previously been reported that Id-negative variants of 38C-13 cells isolated after immunoselection with anti-idiotypic Abs had undergone secondary gene rearrangements (22,23,26). Therefore, we analyzed the rearrangement status of 38C-13 and its spontaneously arising Id-negative variants obtained in vitro.…”
Section: C-13 Cells Undergo Secondary V -J Rearrangements In Culturementioning
confidence: 99%
See 4 more Smart Citations
“…It has previously been reported that Id-negative variants of 38C-13 cells isolated after immunoselection with anti-idiotypic Abs had undergone secondary gene rearrangements (22,23,26). Therefore, we analyzed the rearrangement status of 38C-13 and its spontaneously arising Id-negative variants obtained in vitro.…”
Section: C-13 Cells Undergo Secondary V -J Rearrangements In Culturementioning
confidence: 99%
“…After restriction cleavage, 25 g of DNA were fractionated by electrophoresis on 0.7% agarose gel, transferred to Qiabrane Nylon Plus membrane (Appligene, Strasbourg, France) in 0.4 M NaOH, and hybridized with radiolabeled probes. The probes used are as follows: 3ЈJ 5 is a 620-bp HindIII-NcoI genomic fragment from the murine J -C intron (32); RS, a 800-bp Sau3A fragment (33); 3ЈJ 2, a 279-bp fragment obtained by PCR amplification using the forward primer 5Ј-CTTGTTCACTAAGTCTAAC CTTG-3Ј and reverse primer 5Ј-TTTCCAGTCTGGTCCCATCAC-3Ј; 3ЈJ 4, a 244-bp fragment generated using the forward PCR primer 5Ј-GGGTAACTTGTGTGAATTTGTG-3Ј and reverse primer 5Ј-GACTAT GACATGCCCCTCTC-3Ј; and V 38C, a 213-bp fragment generated using the forward PCR primer 5Ј-AAGGCAAGCCAAGACATTAAC-3Ј and reverse primer 5Ј-CAGATTATCATACTGTAGAC-3Ј (22).…”
Section: Dna Analysismentioning
confidence: 99%
See 3 more Smart Citations